Educational “Looking Glass”, or “They” and “We” - Vladimir F. Zubarev; Gennadiy A. Bondarev (Высшее образование в России)
One of the most important and, according to psychological and pedagogical literature, the least investigated aspects of the domestic system of higher education is the sphere of personal interrelations at the level “teacher – student”. The formation of this type of social relations is a complicated process equally depending on both interested sides, but it is this process that eventually determines the efficiency of the educational process. At present anonymous questioning of both students and teachers is by far the only method of high quality psychodiagnostics of this sphere of educational space. The received findings not only give a more comprehensive idea of the personal characteristics of modern students and the teaching staff of higher schools but can also provide some essential corrective amendments to the organization of the educational process. Anonymous questioning of 400 students of the medical and pediatric faculties of Kursk State Medical University (KSMU) has revealed a number of both quite predictable and fairly unexpected facts concerning the psychological atmosphere at the level “teacher – student”. The received findings to some extent alter the firmly established idea of an elevated ambitiousness of the modern generation of students. Corroborative to it is the objective fact of a lowered personal self-esteem in 38% questioned students of KSMU. The fact of the negative judgment of professional and personal qualities of some teachers (16% of respondents) is alarming and needing thorough consideration and practical conclusions. The comparatively low demand of the recommended to students main academic teaching manuals of the studied disciplines (56%) and the actually unclaimed lectures delivered to them (8%) can be to a great extent explained by their competitive disability in comparison with the short in form but superficial in the contents various kinds of “homebrew” guidance-manuals permanently ranking first in the teachers’ annual rating reports.